INSTITUTIONAL REGULATION OF ECO-MIGRATION POLICY IN GEORGIA - Manvelidze, Irakli (International Journal of Innovative Technologies in Social Science, 2023)
Purpose - The main aim for our research is gaining knowledge of institutional regulation of eco-migration processes in Georgia and, consequently, evaluating the state politics of eco-migration, so as to show off what improving changes can be considered in coming years exactly in the above-mentioned direction. Design/methodology/approach - The research design is based on the institutional approach to studying migration processes. And the empirical analysis was based on the information collected as a result of the study of archival-state documents and interviews in eco-migrant populated areas. The survey was conducted from March 12 to September 25, 2022. Findings - Outcome of our research underlines that the development of institutional provision of eco-migration processes has gone through the different stages during the last centenary in Georgia. As if from the side of government appropriate policy is worked out, however, the research showed that it is necessary to establish a systematic and transparent approach to eco-migration and resettlement by the state, the implementation of which should become the prerogative of both the central government and the municipal administration, which should probably happen in the near future. Originality/value - The scientific novelty of our work is that, for the first time, we studied the historical context of the state policy of eco-migration, the goals of the state policy of eco-migration, the strategy of the state policy of eco-migration and the legal basis of the legal regulation of eco-migration as a process.